Antibody isotypes mediating antigen retention in passively immunized mice. - Phipps, R P (1980)
Antibody isotypes vary in their capacity to mediate retention of a readily catabolized protein antigen, human serum albumin (HSA) in spleen, popliteal lymph node (PLN) and hind foot. Hyperimmune anti-HSA mouse sera were separated into fractions highly enriched for IgM, IgG1 and IgG2 via differential elution from protein A-Sepharose. These fractions were used to immunize normal mice passively. Twenty-four hours later the mice were injected with radio-iodinated HSA into the hind footpad. When the amount of HSA retained in the spleen 6 days later was determined, the potency of various antibody fractions to mediate retention could be ranked IgG2=IgG1 > IgM. The amount of HSA retention mediated by various fractions correlated well with autoradiographic evidence demonstrating localization of HSA in splenic follicles. The localization pattern in PLN was similar to the spleen except that the IgM-containing fraction mediated follicular localization of HSA to a considerable degree. In tendons of the hind foot, IgG1 mediated HSA retention five times better than IgG2 or IgM fractions. The amount of radioactivity found in the liver varied inversely with HSA retention in other locations. The results demonstrate differences in antibody isotype requirements for antigen localization in spleen, regional lymph node and collagenous sites of the hind foot.